Investigating Renal Volume Changes in Type 2 Diabetes Mellitus Using Sonography (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD) worldwide, and it is estimated that more than 20% of type 2 diabetic patients may develop ESRD during their lifetime. The study is a prospective ultrasonography evaluation of kidney volumes in 228 adults with type 2 diabetes and 228 normal non-diabetic adult controls carried out at Aminu Kano Teaching Hospital, Nigeria, from June 2015 to May 2016. The data were analyzed using computer-based SPSS version 23 software for Windows.The 228 patients with type 2 diabetes included 120 (53%) females and 108 (47%) males with a mean age of 47.7 years (range 29–67 years). The 228 normal control participants included 108 (47%) females and 120 (53%) males with a mean age of 46.9 years (range 28–69 years). The age difference between the study and control groups was not statistically significant (p=0.43). The mean renal volumes were significantly higher in the study group (114.10 ± 3.97 ml) compared to the control group (95.34 ± 2.59 ml); this difference was statistically significant (p=0.001). The mean renal volumes were higher in males compared to females in both the study group and the control group (p=0.001). The left mean renal volumes were higher than those of the right in both the study and the control groups (p=0.001). However, there was no significant correlation between renal volume and BMI (p=0.086).The mean renal volume is significantly higher among diabetics compared to normal controls. Patients with type 2 diabetes mellitus have no significant correlation between renal volume and BMI.